O processo comunicativo e os estilos de liderança em escolas TEIP e com contrato de autonomia - Araújo, Filipa (2016)
In this research, two intertwined lines were taken into account: on the one hand, the communication / information flows in the organization (dimension 1) – composed by the subdimensions “sharing strategies and teaching materials”, “the role of ICT in communication”, “the qualities of communication” and “the participation and decision making process” –, and, on the other hand, the leadership styles exercised in each school. A qualitative methodology was used, through discourse analysis of the twenty-five semi-structured interviews that were made to three directors, twelve coordinators and ten teachers from three schools in the north of the country, all of them in disadvantaged territories. The analysis of the interviews shows that in school A the leadership is generally perceived by teachers as autocratic; in school B, a clear trend is not observed, since the data contains elements from a democratic leadership and also from an autocratic leadership; in school C, leadership is perceived by teachers as globally democratic.